9. NORMAL VALUE OF COMMON CAROTID INTIMA-MEDIA THICKNESS IN KOREAN GENERAL POPULATION - Young Jin Youn; Jang-Young Kim; Kyung-Hoon Choe; Junghan Yoon; Seung-Hwan Lee; Kyounghoon Lee; Jun-Won Lee; Sang-Beak Koh; Jongku Park (Artery Research, 2009)
Background: Carotid intima-media thickness (CIMT) is a surrogate marker of cardiovascular disease (CVD). CIMT values ≥75th percentile of normal subjects are considered high and indicative of increased CVD risk. It is a rare data about normal CIMT values in Asian subjects without conventional CVD risk factors, coronary artery disease and cerebrovascular disease. So, we evaluate the normal CIMT values in a community cohort and the relationship between CVD risk factors and CIMT. Methods: We measured CIMT with B-mode ultrasound (Vivid 7, GE Healthcare) in 1,759 subjects aged 40–70 years from ARIRANG study. The normal healthy subject was defined as 1)whom without history of cerebrovascular disease, coronary artery disease, congestive heart failure, dyslipidemia and diabetes mellitus, 2) who was not smoking, 3) whose body mass index <25 kg/m2, 4) whose fasting blood glucose and 2-hour postprandial glucose level were <126 mg/dl and <200mg/dl, respectively, 5) whose total cholesterol level was <220mg/dl, 6) whose systolic blood pressure and diastolic blood pressure was <140/90mmHg. Results: In 1759 subjects, there were 335 of normal healthy subjects (male: 81, female: 254). Mean CIMT and 75% CIMT values showed in table. The mean CIMT values were significantly increased with age (male p trend = 0.002; female p trend <0.001). Mean CIMT showed significantly correlated with age (r = 0.52, p <0.001), abdominal circumference(r = 0.26, p <0.001), systolic blood pressure(r = 0.18, p = 0.001), triglyceride(r = 0.12, p = 0.037) and Framingham’s risk score(r = 0.156, p = 0.000). Table Mean CIMT and 75% CIMT value (mm) Male (n=81) Female (n=254) Age Mean IMT 75% Mean IMT 75% 40∼49 0.546 ± 0.071 0.602 0.482 ± 0.073 0.520 50∼59 0.566 ± 0.133 0.610 0.535 ± 0.105 0.572 60∼70 0.654 ± 0.129 0.710 0.632 ± 0.115 0.687. Conclusion: We defined the normal CIMT values of healthy subjects more strict criteria than other studies and the relationships between risk factors of atherosclerosis and CIMT. Our data suggested that the normal CIMT value of a Korean community cohort is thinner than previously published data from western countries.